2021
DOI: 10.3390/pr9040636
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Cr–Co Alloys Subjected to Porcelain Firing Heat Treatment—In Vitro Study

Abstract: The procedure of ceramics fusion to cobalt–chromium (Co–Cr) base dental crowns affects their corrosion behavior and biological tolerance. This study’s purpose was to comparatively evaluate the effect of heat treatment (HT) applicable for dental ceramics firing on the corrosion properties among Co–Cr base alloys fabricated via different methods: casting (CST), milling soft metal and post sintering (MSM), and selective laser melting (SLM). All specimens were subjected to a heat treatment corresponding to a full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
4
6
1
Order By: Relevance
“…Similarly, after HT, there were no changes in the structure homogeneity/inhomogeneity and in the chemical composition of the superficial layers of both alloys, except for the appearance of oxygen. The present findings are supported by literature [ 45 ]. Moreover, SM-HT exhibited a more homogenous structure and chromium and oxygen distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, after HT, there were no changes in the structure homogeneity/inhomogeneity and in the chemical composition of the superficial layers of both alloys, except for the appearance of oxygen. The present findings are supported by literature [ 45 ]. Moreover, SM-HT exhibited a more homogenous structure and chromium and oxygen distribution.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, Soft Metal (MSM and sintering) exhibited a homogenous structure, on the contrary to MoguCera C (casting). Similar results were obtained by other researchers [ 34 , 38 , 39 , 44 , 45 ]. The highly inhomogeneous structure of MorguCera C resulted in an increased susceptibility to corrosion, due to a less stable passive oxide layer on the surface; as observed by other authors as well [ 16 , 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the high cost of noble metal alloys, base metal alloys, such as cobalt-chromium (Co-Cr), are more extensively used for the metal-ceramic restorations’ construction [ 26 ]. Nowadays, Co–Cr alloys are frequently utilized for dental restorations due to their good biocompatibility [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several research teams evaluated the physical and mechanical properties, as well as the corrosion resistance of MSM Co–Cr. Regarding the corrosion resistance, Rylska et al [ 19 ] reported that among Co–Cr alloys subjected to a porcelain firing procedure, the SLM alloy exhibited the highest corrosion resistance in 0.9 wt.% NaCl, followed by the MSM and the cast alloy. A soft-milled Co–Cr alloy showed a significantly lower Co-ion release than that of its investment cast analogue [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited documentation on the effect of consecutive porcelain firing cycles, such as those employed in the fabrication of metal-ceramic restorations, on the microstructure, corrosion resistance and mechanical properties of dental Co–Cr–Mo fabricated by MSM. Rylska et al [ 19 ] applied a a full porcelain firing schedule on SLM, MSM and Cast Co–Cr, and evaluated the corrosion resistance of the heat-treated alloys, as aforementioned. Önöral et al [ 15 ] conducted repeated firings on Co–Cr alloys fabricated by casting, fully sintered hard alloy milling (FHAM), presintered soft alloy milling (PSAM) and selective laser sintering (SLS); the PSAM-fabricated restorations exhibited the greatest fitting accuracy.…”
Section: Introductionmentioning
confidence: 99%